2022
DOI: 10.1186/s10020-022-00467-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prognostic analysis of biomarkers to predict the progression of pancreatic cancer patients

Abstract: Background Pancreatic cancer (PC) is a malignancy with a poor prognosis and high mortality. Surgical resection is the only “curative” treatment. However, only a minority of patients with PC can obtain surgery. Improving the overall survival (OS) rate of patients with PC is still a major challenge. Molecular biomarkers are a significant approach for diagnostic and predictive use in PCs. Several prediction models have been developed for patients newly diagnosed with PC that is operable or patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…Previous research indicates that immunotherapy may be a promising strategy for PCa [38]. Recently, immune-related genes, such as FN1 and ANXA1, have been identified as prognostic indicators of PCa [39]. Nevertheless, the prognostic significance of these genes needs to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that immunotherapy may be a promising strategy for PCa [38]. Recently, immune-related genes, such as FN1 and ANXA1, have been identified as prognostic indicators of PCa [39]. Nevertheless, the prognostic significance of these genes needs to be further verified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both ANXA1 expression and S100A9 overexpression by naïve macrophages promote immunosuppression, resist inflammatory processes, and enhance the ability of macrophages to polarize toward the M2 phenotype [ 24 , 109 ]. Therefore, targeting S100A9 and ANXA1 is a potential strategy for clearing TAMs [ 110 , 111 ]. Besides inhibiting signaling molecules that induce M2 macrophage polarization and downregulating M2 macrophage production, studies have also elucidated the mechanisms of directly targeting the recognition signals of M2 macrophages and promoting the apoptotic process of M2 macrophages.…”
Section: Strategies For Targeting Macrophages In the Treatment Of Sol...mentioning
confidence: 99%
“…The Kyoto Encyclopedia of Genes and Genomes (KEGG) Enrichment Analysis is a practical resource for the analytical study of gene functions and associated high-level genome functional information. To better understand the carcinogenesis of mRNA, the ClusterProfiler package (version: 3.18.0) of R was employed to analyze the enrichment of the KEGG pathway as our previous described ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using gene expression markers, TIDE provides insight into two different mechanisms of tumor immune escape, namely dysfunction of tumor-infiltrating cytotoxic T lymphocytes (CTL) and exclusion of CTL by immunosuppressive factors. It has been shown that high TIDE scores are associated with poor immunocheckpoint blockade therapy (ICB) efficacy and short survival following ICB treatment ( 26 ). Therefore, TIDE score is a novel method for predicting ICB responses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation